Answer:
2÷4 is equal to 0.5.
- Take the first digit of the dividend from the left. Check if this digit is greater than or equal to the divisor.
- Then divide it by the divisor and write the answer on top as the quotient.
- Subtract the result from the digit and write the difference below.
Please Mark Brainliest If This Helped!
We want a solution in the form
![y=\displaystyle\sum_{n\ge0}a_nx^n](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7Da_nx%5En)
with derivatives
![y'=\displaystyle\sum_{n\ge0}(n+1)a_{n+1}x^n](https://tex.z-dn.net/?f=y%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B1%29a_%7Bn%2B1%7Dx%5En)
![y''=\displaystyle\sum_{n\ge0}(n+2)(n+1)a_{n+2}x^n](https://tex.z-dn.net/?f=y%27%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B2%29%28n%2B1%29a_%7Bn%2B2%7Dx%5En)
Substituting
and its derivatives into the ODE,
![y''-2xy'+2y=0](https://tex.z-dn.net/?f=y%27%27-2xy%27%2B2y%3D0)
gives
![\displaystyle\sum_{n\ge0}(n+2)(n+1)a_{n+2}x^n-2\sum_{n\ge0}(n+1)a_{n+1}x^{n+1}+2\sum_{n\ge0}a_nx^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B2%29%28n%2B1%29a_%7Bn%2B2%7Dx%5En-2%5Csum_%7Bn%5Cge0%7D%28n%2B1%29a_%7Bn%2B1%7Dx%5E%7Bn%2B1%7D%2B2%5Csum_%7Bn%5Cge0%7Da_nx%5En%3D0)
Shift the index on the second sum to have it start at
:
![\displaystyle\sum_{n\ge0}(n+1)a_{n+1}x^{n+1}=\sum_{n\ge1}na_nx^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B1%29a_%7Bn%2B1%7Dx%5E%7Bn%2B1%7D%3D%5Csum_%7Bn%5Cge1%7Dna_nx%5En)
and take the first term out of the other two sums. Then we can consolidate the sums into one that starts at
:
![\displaystyle(2a_2+2a_0)+\sum_{n\ge1}\bigg[(n+2)(n+1)a_{n+2}+(2-2n)a_n\bigg]x^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%282a_2%2B2a_0%29%2B%5Csum_%7Bn%5Cge1%7D%5Cbigg%5B%28n%2B2%29%28n%2B1%29a_%7Bn%2B2%7D%2B%282-2n%29a_n%5Cbigg%5Dx%5En%3D0)
and so the coefficients in the series solution are given by the recurrence,
![\begin{cases}a_0=y(0)\\a_1=y'(0)\\(n+2)(n+1)a_{n+2}=2(n-1)a_n&\text{for }n\ge0\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_0%3Dy%280%29%5C%5Ca_1%3Dy%27%280%29%5C%5C%28n%2B2%29%28n%2B1%29a_%7Bn%2B2%7D%3D2%28n-1%29a_n%26%5Ctext%7Bfor%20%7Dn%5Cge0%5Cend%7Bcases%7D)
or more simply, for
,
![a_n=\dfrac{2(n-3)}{n(n-1)}a_{n-2}](https://tex.z-dn.net/?f=a_n%3D%5Cdfrac%7B2%28n-3%29%7D%7Bn%28n-1%29%7Da_%7Bn-2%7D)
Note the dependency between every other coefficient. Consider the two cases,
- If
, where
is an integer, then
![k=0\implies n=0\implies a_0=a_0](https://tex.z-dn.net/?f=k%3D0%5Cimplies%20n%3D0%5Cimplies%20a_0%3Da_0)
![k=1\implies n=2\implies a_2=-a_0=2^1\dfrac{(-1)}{2!}a_0](https://tex.z-dn.net/?f=k%3D1%5Cimplies%20n%3D2%5Cimplies%20a_2%3D-a_0%3D2%5E1%5Cdfrac%7B%28-1%29%7D%7B2%21%7Da_0)
![k=2\implies n=4\implies a_4=\dfrac{2\cdot1}{4\cdot3}a_2=2^2\dfrac{1\cdot(-1)}{4!}a_0](https://tex.z-dn.net/?f=k%3D2%5Cimplies%20n%3D4%5Cimplies%20a_4%3D%5Cdfrac%7B2%5Ccdot1%7D%7B4%5Ccdot3%7Da_2%3D2%5E2%5Cdfrac%7B1%5Ccdot%28-1%29%7D%7B4%21%7Da_0)
![k=3\implies n=6\implies a_6=\dfrac{2\cdot3}{6\cdot5}a_4=2^3\dfrac{3\cdot1\cdot(-1)}{6!}a_0](https://tex.z-dn.net/?f=k%3D3%5Cimplies%20n%3D6%5Cimplies%20a_6%3D%5Cdfrac%7B2%5Ccdot3%7D%7B6%5Ccdot5%7Da_4%3D2%5E3%5Cdfrac%7B3%5Ccdot1%5Ccdot%28-1%29%7D%7B6%21%7Da_0)
![k=4\implies n=8\implies a_8=\dfrac{2\cdot5}{8\cdot7}a_6=2^4\dfrac{5\cdot3\cdot1\cdot(-1)}{8!}a_0](https://tex.z-dn.net/?f=k%3D4%5Cimplies%20n%3D8%5Cimplies%20a_8%3D%5Cdfrac%7B2%5Ccdot5%7D%7B8%5Ccdot7%7Da_6%3D2%5E4%5Cdfrac%7B5%5Ccdot3%5Ccdot1%5Ccdot%28-1%29%7D%7B8%21%7Da_0)
and so on, with the general pattern
![a_{2k}=\dfrac{2^ka_0}{(2k)!}\displaystyle\prod_{i=1}^k(2i-3)](https://tex.z-dn.net/?f=a_%7B2k%7D%3D%5Cdfrac%7B2%5Eka_0%7D%7B%282k%29%21%7D%5Cdisplaystyle%5Cprod_%7Bi%3D1%7D%5Ek%282i-3%29)
- If
, then
![k=0\implies n=1\implies a_1=a_1](https://tex.z-dn.net/?f=k%3D0%5Cimplies%20n%3D1%5Cimplies%20a_1%3Da_1)
![k=1\implies n=3\implies a_3=\dfrac{2\cdot0}{3\cdot2}a_1=0](https://tex.z-dn.net/?f=k%3D1%5Cimplies%20n%3D3%5Cimplies%20a_3%3D%5Cdfrac%7B2%5Ccdot0%7D%7B3%5Ccdot2%7Da_1%3D0)
and we would see that
for all
.
So we have
![y(x)=\displaystyle\sum_{k\ge0}\bigg[a_{2k}x^{2k}+a_{2k+1}x^{2k+1}\bigg]](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdisplaystyle%5Csum_%7Bk%5Cge0%7D%5Cbigg%5Ba_%7B2k%7Dx%5E%7B2k%7D%2Ba_%7B2k%2B1%7Dx%5E%7B2k%2B1%7D%5Cbigg%5D)
so that one solution is
![\boxed{y_1(x)=\displaystyle a_0\sum_{k\ge0}\frac{2^k\prod\limits_{i=1}^k(2i-3)}{(2k)!}x^{2k}}](https://tex.z-dn.net/?f=%5Cboxed%7By_1%28x%29%3D%5Cdisplaystyle%20a_0%5Csum_%7Bk%5Cge0%7D%5Cfrac%7B2%5Ek%5Cprod%5Climits_%7Bi%3D1%7D%5Ek%282i-3%29%7D%7B%282k%29%21%7Dx%5E%7B2k%7D%7D)
and the other is
![\boxed{y_2(x)=a_1x}](https://tex.z-dn.net/?f=%5Cboxed%7By_2%28x%29%3Da_1x%7D)
I've attached a plot of the exact and series solutions below with
,
, and
to demonstrate that the series solution converges to the exact one.
Answer:
No solution
Step-by-step explanation:
by criss cross method, 6(x+3) = 6(4+x)
6x+18 = 24+6x
6x-6x = 24-18
0=6 no solution
1/2 would be rounded to 1 and 4/6 would be rounded to 1
Answer:
Step-by-step explanation:
D